Access to Aboriginal Community-Controlled Primary Health Organizations Can Explain Some of the Higher Pap Test Participation Among Aboriginal and Torres Strait Islander Women in North Queensland, Australia - Dasgupta, Paramita; Condon, John R.; Whop, Lisa J.; Aitken, Joanne F.; Garvey, Gail; Wenitong, Mark; Baade, Peter D. (Frontiers in Oncology, 2021)
Background Aboriginal and Torres Strait Islander Community-Controlled Health Organisations (ACCHOs) provide culturally appropriate primary care for Aboriginal and Torres Strait Islander peoples in Australia. The population of North Queensland has a higher proportion of Aboriginal and Torres Strait Islander peoples, a greater population coverage of ACCHOs, and higher cervical screening participation than the Rest of Queensland. The association between regional differences in the use of ACCHOs for cervical screening and variations in screening participation among Aboriginal and Torres Strait Islander women is currently unknown. Methods Population-based study of 1,107,233 women, aged 20-69 years who underwent cervical screening between 2013 and 2017. Of these women, 132,972 (12%) were from North Queensland, of which 9% were identified as Aboriginal and Torres Strait Islander women (2% Rest of Queensland) through linkage to hospital records. Regional differentials in screening by Aboriginal and Torres Strait Islander status were quantified using participation rate ratios (PRR) with 95% confidence intervals (CI) from negative binomial regression models. Logistic regression was used to identify factors associated with Aboriginal and Torres Strait Islander women being screened at ACCHOs. Results Aboriginal and Torres Strait Islander women from North Queensland (versus) Rest of Queensland had higher odds of screening at ACCHOs after adjusting for age and area-level variables. After adjustment for non-ACCHO variables, the regional differential in screening among Aboriginal and Torres Strait Islander women was significantly higher (PRR 1.28, 95% CI 1.20-1.37) than among other Australian women (PRR=1.11 [1.02-1.18]), but was attenuated on further adjustment for ACCHO variables, (PRR=1.15, [1.03-1.28]) to become similar to the corresponding point estimate for other Australian women (PRR=1.09, [1.01-1.20]). However, the significant interaction between Aboriginal and Torres Strait Islander status and region (p<0.001) remained, possibly reflecting the large cohort size. Screening participation increased with better access to health services for all women. Conclusions Improving access to primary health care for Aboriginal and Torres Strait Islander women, especially through ACCHOs, may reduce existing disparities in cervical screening participation. Further gains will require greater levels of local community engagement and understanding of the experiences of screened Aboriginal and Torres Strait Islander women to inform effective interventions.